Application of MT method of Mahalanobis-Taguchi system in methadone flexi dispensing program - S. N. A. M., Zaini; Mohd Yazid, Abu; Nur Najmiyah, Jaafar; S. K. M., Saad (Malaysian Technical Universities Network (MTUN), 2023)
Patient under methadone flexi dispensing (MFlex) program are required to perform blood tests like lipid profile. To verify the patient does have a lipid disorder, a doctor analyses 3 parameters such as cholesterol, HDL cholesterol, and LDL cholesterol. However, the present system lacks a robust ecology for categorization and optimization due to imprecise measuring methods and a lack of rationale for major elements that impact diagnostic accuracy. The goal is to implement the Mahalanobis-Taguchi system (MTS) into the MFlex programme. The data was acquired at the Bandar Pekan clinic and included 34 lipid profile measures. For classification and optimization, two categories of MTS techniques are being used, which are RT-Method and T-Method. As a result of the lipid profile analysis, the healthy Mahalanobis distance (MD) is 1.0000, whereas the unhealthy MD is 79.5876. Positive contributions are made by parameters 1, 3, 4, 6, 7, 8, 9, 11, 12, 17, 18, 23, 26, 27, 28, 30, 31, 33, and 34. 15 unknown samples were diagnosed with varying degrees of positive and negative contribution to obtain a smaller MD. The best recommended way has been typed 5 from overall 6 modifications. Finally, the pharmacist acknowledged that MTS could tackle the issue of MFlex programme categorization.